General relativity in two dimensions: A Hamilton-Jacobi analysis - Bertin, M. C. [UNESP]; Pimentel, B. M. [UNESP]; Pompeia, P. J. (Academic Press Inc. Elsevier B.V., 2010)
We analyzed the constraint structure of the Einstein-Hilbert first-order action in two dimensions using the Hamilton-Jacobi approach. We were able to find a set of involutive, as well as a set of non-involutive constraints. Using generalized brackets we showed how to assure integrability of the theory, to eliminate the set of non-involutive constraints and how to build the field equations. (c) 2010 Elsevier B.V. All rights reserved.
Keywords: Hamilton-Jacobi; Constraints; General relativity; Two dimensions